Genetic control of yield components in green beans (Phaseolus vulgaris L.) (2023)
. For most of the traits, except yield per plant, the additive-dominant model was adequate. Non-additive effects with overdominance controlled the number of pods per plant, pod length, and mean pod weight. Most of the characters presented an unequal proportion of positive and negative genes in the loci (H1 < H2 ). The asymmetric distribution of genes in the parents (H2 /4H1 ) was below the maximum value (0.25), except for the character “number of pods per plant”. The KD/KR ratio confirmed for most of the traits that there was an excess of recessive alleles over dominant alleles. Dominance effects (h2 ) for most characters suggested that the substantial contribution of dominance was not due to heterogeneity of loci in these characters. The narrow-sense heritability was moderate to low. The correlation coefficient r (Yr; Wr + Vr) indicated that dominant genes were responsible for the increased number of pods per plant and recessive genes for increased pod length and mean pod weight. Conclusions. Conventional breeding methods like pedigree selection could be employed to improve the characters “pod length” and “mean pod weight”, and for the number of pods per plant, management of segregating populations should employ the single-seeded descent method.